Studies on capsule shattering character in sesame (Sesamum indicum L.): Studies on capsule shattering character in sesame (Sesamum indicum L.) - M MOHAMMED IMRAN; MANASI DASH; P MANJUNATH; M SURYA PRAKASHREDDY (Journal of Oilseeds Research, 2020)
Thirty five Indian sesame genotypes were evaluated for their genetic diversity for seed yield and yield attributing characters as well as capsule shattering characters. The analysis of variance revealed highly significant differences among the genotypes for all twenty characters. High magnitude of PCV and GCV was recorded for capsule split and opening before drying. Further, potential seed weight has the highest contribution to total divergence followed by capsule split before drying, retained seed weight, unattached seed weight and seed weight/capsule indicating their importance in the choice of parents for developing semi shattering genotypes.